Food Price Policy and Equity - Ghai, Dharam; Smith, Lawrence (International Food Policy Research Institute, 1987)
Policies for food are much more relevant to equity considerations than policies for most other commodities. Not only is food essential for survival, but the poor spend a higher proportion of their income on food than the rich. A change in the price of food has a proportionally greater impact on their real income and welfare. Food also is a source of income for a large proportion of the population in developing countries. Consequently, the focus here is primarily on agricultural pricing, which some claim is a major factor underlying current food problems in Africa.